Hydrological stability drives both local and regional diversity patterns in rock pool metacommunities. Issue 6 (11th November 2014) - Brendonck, Luc; Jocqué, Merlijn; Tuytens, Karen; Timms, Brian V.; Vanschoenwinkel, Bram
<x xml:space="preserve">Abstract</x> A main challenge associated with macro ecological gradients such as the latitudinal diversity gradient (LDG) is that proxies of potential underlying processes are often correlated at large scales. One way to reliably identify contributing processes is to show that they can lead to similar responses at local scales. Using a set of invertebrate communities from rock pool clusters along a latitudinal gradient in Australia, we investigated the importance of hydrological stability for explaining both local and regional diversity patterns in this habitat. Results show that, at both local and regional scales, habitat stability in terms of the frequency and length of inundations was strongly correlated to local alpha diversity in individual pools and to gamma diversity at the level of pool clusters. Additionally, partitioning beta diversity into components of nestedness and species turnover revealed that communities in unstable habitats were nested subsets of communities in more stable habitats. Overall, this study provides convincing mechanistic support for the climate stability hypothesis as a potential explanation for the LDG in this system. Results also indicate that when there is enough time for dispersal and colonization, regional processes can be relatively unimportant compared to local processes to explain large scale diversity patterns.